2014
DOI: 10.1016/j.nicl.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Progressive white matter changes following anterior temporal lobe resection for epilepsy

Abstract: Anterior temporal lobe resection (ATLR) is an effective treatment for refractory temporal lobe epilepsy (TLE). Widespread abnormalities in diffusion parameters involving the ipsilateral temporal lobe white matter and extending into extratemporal white matter have been shown in cross-sectional studies in TLE. However longitudinal changes following surgery have been less well addressed. We systematically assess diffusion changes in white matter in patients with TLE in comparison to controls before surgery and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
44
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 37 publications
10
44
1
1
Order By: Relevance
“…Regarding FA decreases, a symmetrical pattern was observed in LATL and RATL patients involving decreases in the fornix, SLF, UNC, callosum, inferior fronto-occipital and external capsule. Evidence of decreased FA post-surgery in ATL has been reported for all the above tracts in prior studies [25][30], [49]. In particular, all studies agree in finding FA disruptions in the fornix, which we consistently found to be the area of greatest diminishment for both ATL groups.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding FA decreases, a symmetrical pattern was observed in LATL and RATL patients involving decreases in the fornix, SLF, UNC, callosum, inferior fronto-occipital and external capsule. Evidence of decreased FA post-surgery in ATL has been reported for all the above tracts in prior studies [25][30], [49]. In particular, all studies agree in finding FA disruptions in the fornix, which we consistently found to be the area of greatest diminishment for both ATL groups.…”
Section: Discussionsupporting
confidence: 87%
“…Data from the current study in a similar cohort suggest that despite apparent normalization of WM DTI metrics at 1 year, alteration in WM microstructure compared to controls is evident about 8 years after PFS, and that this alteration is accompanied by apparent increases in the coherence of the remaining WM structure. Similar findings of FA increase, often accompanied by an increase in AD, have also been reported several months after brain insult in the form of brain surgery, stroke, and traumatic brain injury 30, 31, 32, 33. It is tempting to suggest that this reorganization of the remaining WM structure is the brain's attempt to maintain efficient organization in the face of an event disruptive to the normal trajectory of maturation, and one that has served to maintain neurologic and cognitive function as observed in our cohort.…”
Section: Discussionsupporting
confidence: 78%
“…Similar findings of FA increase, often accompanied by an increase in AD, have also been reported several months after brain insult in the form of brain surgery, stroke, and traumatic brain injury. [30][31][32][33] It is tempting to suggest that this reorganization of the remaining WM structure is the brain's attempt to maintain efficient organization in the face of an event disruptive to the normal trajectory of maturation, and one that has served to maintain neurologic and cognitive function as observed in our cohort. The biophysical characteristics of WM affecting the diffusivity parameters on in vivo DTI are likely to be complex and multifarious.…”
Section: Discussionmentioning
confidence: 90%
“…167,172,199,201 Detecting Postoperative Changes Acute and chronic diffusion abnormalities, ipsilateral and contralateral to the epileptic focus, have also been seen after ATLR. [202][203][204][205][206] In patients undergoing ATLR, increases in FA in ipsilateral ventromedial language network were shown for the first time by Yogarajah and colleagues 203 (Fig. 4i) at 4 months after surgery, and later confirmed by Winston and colleagues.…”
Section: Hs Resultsmentioning
confidence: 78%
“…4i) at 4 months after surgery, and later confirmed by Winston and colleagues. 206 These changes are correlated with postoperative verbal fluency and naming test scores. The larger the increase in parallel diffusivity in ventromedial language network area, the smaller the decrease in language proficiency postsurgically, reflecting plasticity in language networks in response to ATLR (see Fig.…”
Section: Hs Resultsmentioning
confidence: 98%